Antiangiogenic factors and maternal hemodynamics during intensive hemodialysis in pregnancy. Issue 4 (1st April 2013) - Cornelis, Tom; Spaanderman, Marc; Beerenhout, Charles; Perschel, Frank H.; Verlohren, Stefan; Schalkwijk, Casper G.; van der Sande, Frank M.; Kooman, Jeroen P.; Hladunewich, Michelle
Abstract: We report on a 21‐year‐old pregnant patient with IgA nephropathy who was initiated on intensive hemodialysis (8 hours of hemodialysis 3 times a week) at a gestational age of 26 weeks on the basis of worsening kidney function resulting in rapidly progressive fatigue and difficulties in metabolic control. Throughout the pregnancy, and while on intensive hemodialysis, 24‐hour ambulatory blood pressure control was within the target, and results of weekly 24‐hour measurement of central hemodynamics and pulse wave velocity, and of serial levels of circulating (anti‐)angiogenic factors were comparable to normal pregnancies. Estimated fetal growth evolved along the 50th percentile, and no polyhydramnios was detected. After induction for a sudden, unexplained increase in blood pressure, she delivered a healthy boy of 2480 g at a gestational age of 36 weeks. This case adds to the expanding literature that supports the use of intensive hemodialysis in pregnant patients with end‐stage renal disease and illustrates, for the first time, the potential use of serial (anti‐) angiogenic factors and 24‐hour measurements of blood pressure and hemodynamic indices in order to facilitate monitoring of these complicated patients.